The Effect of Non-Tariff Measures on Vietnam Exports - Ngo, Thuy Ha (American Journal of Social Sciences and Humanities, 2020)
Although tariff rates have gradually decreased over time, non-tariff measures (NTMs) have proliferated both in quantity and diversification. The complex and multifaceted trade policies have an effect on international trade, especially for developing countries’ trade since NTMs are mostly operated by developed countries. Vietnam, like other developing countries, needs to comply with NTM requirements and understand their effects. This paper, firstly, reviews the liberalization process of Vietnam through both traditional trade policies and NTMs. It, secondly, assesses the pattern of NTMs held by various income countries to identify the challenges in the process of integration to the global economy of Vietnam under the conditions of increasing more NTMs. Last but not least, by using technical barriers to trade (TBT) data (which sourced from WTO for the period 1995 to 2012) of ASEAN members, it is found that if ASEAN members increase the measures, TBT will have a negative lag impact on Vietnam’s exports.